Intervención educativa sobre prevención de accidentes en el hogar y prácticas preventivas en madres del Pueblo Joven Nuevo Versalles Iquitos 2021 - Ramirez Pérez, Jimena Lizeth (2025)
The objective of the study was to evaluate the effect of the educational intervention on the prevention of accidents at home and preventive practices in mothers of children from 3 to 6 years of age in Pueblo Joven Nuevo Versalles of Iquitos 2021. The study is quantitative, the design of a quasi experimental type with a single pre- and post-test group, the population consisted of 1,500 mothers with children aged 3 to 6 years, the sample consisterd of 30 mothers with children aged 3 to 6 years. The techniques were the interview and the observation, and the instruments were the observation guide that had a validity of 93.2% and reliability of 91,5%, and the educational intervention "You decide no more accidents in your home". The results show that before the educational intervention, the majority 76,7% of the mothers had incorrect preventive practices of accidents in the home, while after the educational intervention, the majority 80.0% had preventive practices of accidents in the home. correct home. To verify the hypothesis, the t-student statistical test was applied for related samples, obtaining p-value = 0,000; with differences between means of 21,6 to 30,4 between the pre and post test (mean 8,7), accepting the hypothesis. Therefore, it is concluded that the educational intervention was effective in the prevention of accidents at home in mothers of children from 3 to 6 years of the Pueblo Joven Nuevo Versalles of Iquitos 2021.